Sex and Secularism - Scott, Joan Wallach 1941-; Scott, Joan Wallach 1941- (Book collections on Project MUSE., 2018)
Women and religion -- Reproductive futurism -- Political emancipation -- From the Cold War to the clash of civilizations -- Sexual emancipation.